2023
DOI: 10.3390/ijerph20095668
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on the Impact of Statin Treatment in HIV Patients on Antiretroviral Therapy

Abstract: The rate of new human immunodeficiency virus (HIV) infections globally is alarming. Although antiretroviral therapy (ART) improves the quality of life among this group of patients, ARTs are associated with risk of cardiovascular diseases (CVD). Moreover, virally suppressed patients still experience immune activation associated with HIV migration from reservoir sites. Statins are widely recommended as therapeutic agents to control ART-related CVD; however, their impacts on the cluster of differentiation (CD)4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The heterogeneity among studies was tested by the I 2 test and Q statistical test. On account of the high heterogeneity of collected studies in our research (I 2 > 75%, p < 0.1), [10][11][12][13][14] DerSimonian-Laird random-effects model was used to calculate the pooled odds ratios. Meta-regression analysis based on multiple factors (publication year, province, sex ratio, and sample size) was performed to find the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity among studies was tested by the I 2 test and Q statistical test. On account of the high heterogeneity of collected studies in our research (I 2 > 75%, p < 0.1), [10][11][12][13][14] DerSimonian-Laird random-effects model was used to calculate the pooled odds ratios. Meta-regression analysis based on multiple factors (publication year, province, sex ratio, and sample size) was performed to find the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing interest in implementing effective interventions to address INR in HIV patients. While certain studies suggest that drug therapies can enhance the immune response by suppressing abnormal immune activation (21), numerous studies have demonstrated the limited therapeutic e cacy of immunomodulators such as statins (22), mesalazine (23), rifaximin (24), and rapamycin (25) in improving INR. Currently, there is a scarcity of effective intervention measures for INR.…”
Section: Introductionmentioning
confidence: 99%